Understanding the relationship transitions and associated end of life clinical needs of young adults with life-limiting illnesses: A triangulated longitudinal qualitative study. (4th October 2016) - Johnston, Bridget; Jindal-Snape, Divya; Pringle, Jan; Gold, Libby; Grant, Jayne; Dempsey, Raymond; Scott, Ros; Carragher, Pat
Background: Care of young adults with life-limiting illnesses can often be complex due to the fact that they are growing and developing within the continuing presence of their illness. There is little research conducted nationally and internationally, which has examined the life issues of young adults or taken a longitudinal approach to understand such issues over a period of time. Aim: To gain clear understanding of one particular and pertinent life issue—relationship transition—occurring in the context of being a young adult with a life-limiting illness and the clinical needs arising from this. Design: This was a triangulated, longitudinal, qualitative study involving young adults with life-limiting illnesses and their significant others, namely, family members and healthcare professionals. Semi-structured interviews were conducted with participants and analysed using thematic analysis. Clinical case note reviews were also carried out. Setting/participants: A total of 12 young adults (aged between 17 and 23 years) from 2 hospices and 22 nominated significant others participated in a total of 58 interviews. Results: Thematic analysis revealed 4 main themes and 11 subthemes. The main themes were 'Dependence dichotomy', 'In it together', 'Biographical uncertainty', and 'Conserving integrity'. These themes helped to establish the nature of relationship transitions that the young adult participants from the study experienced and additionally allowed insight into their possible needs at their end of life. Conclusion: This study has identified the nature of relationship transitions pertinent to young adults and has highlighted associated end of life clinical needs. This study can influence further research into the transitions and end of life needs of this particular patient group receiving palliative care, while informing the lacking evidence base which exists internationally.